Financial hardship among individuals with serious mental illness. (December 2019) - Spivak, Stanislav; Cullen, Bernadette; Eaton, William W.; Rodriguez, Katrina; Mojtabai, Ramin
Highlights: In this study nearly sixty percent of adults with serious mental illness experienced financial hardship. The experience of hardship is more common in women with serious mental illness. Among individuals with serious mental illness financial hardship is associated with higher stigma and higher psychiatric symptom burden. Among individuals with serious mental illness financial hardship is associated with increased barriers to care and increased emergency department utilization. Abstract: This study explored financial hardship, defined as difficulty in obtaining food, shelter, or medicine in the past 12 months and its personal and clinical correlates in individuals with serious mental illness (SMI) in a sample of 271 adults with SMI newly admitted to two inner city community mental health centers. The study found that 59 percent ( n  = 161) reported experiencing financial hardship in the past 12 months. Patients with financial hardship were more likely to be female, to experience self-stigma, to experience medical care delays, and to use emergency services. Patients who experienced financial hardship typically had more severe psychiatric symptoms, including depressive symptoms, emotional lability, and interpersonal problems. Financial hardship persisted in nearly half of those with hardship interviewed a year later. The findings highlight the role of multiple social and economic challenges that the SMI patients face in recovery from serious mental illness and the importance of awareness of such challenges by providers treating this population. Though mental health treatment may help alleviate the psychiatric symptoms it alone is not sufficient in addressing persistent hardship. These findings highlight the need for multidisciplinary interventions in order to better serve this vulnerable population.